Pharmacokinetics and safety profiles of beinaglutide injection, a recombinant human GLP-1, in adults with overweight/obesity: results from a phase I clinical trial - Lin, Pingping; Li, Chengqian; Liu, Yanping; Sun, Feifei; Hsieh, Tsung-Han; Lin Zhang,; Ma, Yaping; Gao, Xiaomeng; Yu, Qing; Cao, Yu (Frontiers in Pharmacology, 2024)
Background: Beinaglutide, whose active ingredient is rhGLP-1, has been widely used as a pharmacological therapy for T2DM. We explored the safety and pharmacokinetics of beinaglutide in Chinese overweight/obese volunteers to lay a foundation for clinical applications of beinaglutide as an anti-obesity drug.Methods: An open-label, single center, multiple ascending dose phase I clinical trial was conducted in 16 overweight/obese Chinese volunteers. The plasma concentrations of beinaglutide were determined by a validated ELISA method and the pharmacokinetic parameters were estimated via non-compartmental analysis methods. Adverse events were also recorded.Results: Beinaglutide sequentially multiple dosing (three times daily) at different doses were generally well tolerated, without serious AEs leading to discontinuation of the trial.After multiple subcutaneous injections of different doses (0.1 mg, 0.14 mg and 0.2 mg), the average blood concentration of beinaglutide with or without baseline correction showed a similar trend among different dose groups on different study days. After reaching the peak concentration around 15 minutes, it began to decrease, and the median of T max and T max,adj was 10 -15 minutes. The exposure in vivo increased in proportion to the dosage increment, demonstrating linear pharmacokinetic characteristics. There were no statistically significant differences in the main PK parameters and no accumulation of beinaglutide after multiple dosing. After multiple subcutaneous injections, a gender difference was observed, while no differences in BMI were found under the grouping conditions.The safety profile and pharmacokinetic properties support further development and clinical applications of beinaglutide as an anti-obesity drug.